Correction to: Synergic Effect of Catalyst/Binder in Passivation Side-Products of Li-Oxygen Cells (Journal of Solid State Electrochemistry, 2019 23 12 (3309-3317), 10.1007/S10008-019-04417-Z) - Aguirre-Quintana, M; Aguirre-Quintana, M; Herrera-Diaz, F; Herrera-Diaz, F; Márquez-Mandiola, P; Márquez-Mandiola, P (Springer, 2020)
The Authors regret that, in the published version, Figure 2 was substituted by Figure 1. The correct Figure 2 is reported below: (Figure presented.) Moreover, if possible, the Authors would like the following acknowledgement added: The Authors wish to thank Dr. Freddy Celis for Raman analysis. This work was supported by Conicyt-PCHA; Doctorado Nacional, 2014, Dicyt_USACH 051831EM_DAS, Fondecyt 1131019 and 1160324 projects (Prof María Jesús Aguirre), as well as ENEA PAR 2017 (Prof. Silvia Bodoardo). The authors apologize for any caused inconvenience. © 2019, Springer-Verlag GmbH Germany, part of Springer Nature.